A survey on the use of mobile phones of the University of the Philippines Diliman students for library and academic purposes - Tomalon, Thaddeus H. Jr (School of Library and Information Studies, University of the Philippines Diliman, 2008)
The mobile phone being the most ubiquitous technological device has been the subject of many studies in different areas of the academic realm. Its function as a communication tool has been applauded since it started. There are members of the academic community who nod at the use of mobile phones during school hours. Yet it is not surprising that students will find ways of utilizing this innovation in unexpected ways.